Implikasi Pendidikan dalam Q.S. Luqman Ayat 13 terhadap Komunikasi Interpersonal Orang Tua dan Anak - Wildan Mansur; Eko Subiantoro (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Process of delivering information, thoughts and attitudes aim to achieve mutual understanding, regarding the problems to be discussed, which in turn is expected to change behavior. The type of approach in this writing is library research, which is taking research materials from several books or other literature that supports this research. The approach used is a phenomenological approach, which is trying to understand the meaning of interactions between human beings in terms of education. So, the emphasis is on an interactive understanding of the phenomena that occur. The results of this study indicate that the editorial